Analisis Keterlibatan Mahasiswa Dalam Pembelajaran Berbasis Proyek - Farida, Mustika Khurotul; Setyosari, Punaji; Aulia, Fikri (Universitas Negeri Malang, 2024)
Student involvement in the learning process is an important thing that can have a big impact on the success and effectiveness of learning. The learning model that can be used is project-based learning which can be carried out collaboratively by creating projects that are in accordance with the learning objectives that have been set. This research aims to describe the level of student involvement in project-based learning based on three aspects with each indicator. This research uses descriptive quantitative methods. Research data was obtained from a questionnaire distributed to educational technology students at the State University of Malang in the third and fifth semesters. The results of the research show that the level of student involvement of most students is in the medium category in the three aspects of involvement, including cognitive aspects, behavioral aspects and emotional aspects. In the cognitive aspect students make efforts to understand the material and mastery of skills, in the behavioral aspect students show positive behavior such as paying attention and discussing, in the emotional aspect students show feelings of interest, happiness, sadness and anxiety during learning and the process of working on projects. Abstrak Keterlibatan mahasiswa dalam proses pembelajaran merupakan suatu hal penting yang dapat berdampak besar untuk keberhasilan dan keefektifan pembelajaran. Model yang pembelajaran yang dapat digunakan adalah pembelajaran berbasis proyek yang dapat dilakukan secara kolaboratif dengan membuat proyek yang sesuai dengan tujuan pembelajaran yang telah ditetapkan. Penelitian ini bertujuan untuk mendeskripsikan tingkat keterlibatan mahasiswa dalam pembelajaran berbasis proyek berdasarkan 3 aspek dengan masing-masing indikator. Penelitian ini menggunakan metode kuantitatif deskriptif. Data penelitian diperoleh dari kuesioner angket yang disebar kepada mahasiswa S1 Teknologi Pendidikan Universitas Negeri Malang angkatan 2022 dan 2023. Hasil penelitian menunjukkan bahwa tingkat keterlibatan mahasiswa sebagian besar mahasiswa berada dalam kategori sedang pada ketiga aspek keterlibatan (aspek kognitif, aspek perilaku, dan aspek emosional). Pada aspek kognitif mahasiswa memberikan usahanya untuk memahami materi dan penguasaan keterampilan, pada aspek perilaku mahasiswa menunjukkan perilaku positif seperti memperhatikan dan berdiskusi, pada aspek emosional mahasiswa menunjukkan perasaan minat, senang, sedih, dan cemas saat pembelajaran maupun proses pengerjaan proyek.